Interaction : foreign policy and public policy - Feigert, Frank B.; Piper, Don C.; Terchek, Ronald (Washington : American Enterprise Institute for Public Policy Research, 1983)
The publication is divided into two parts. Part one- The policy-making process which comprises: public opinion and foreign policy; congressional response to presidential vetoes in foreign and defense policy; foreign and domestic policy linkages; and strategic intelligence and the formulation of public policy. Part two- Substantive issues entail the United States Immigration Policy at the cross roads; Foreign Direct Investment in the United States; American politics and the law of the sea; human rights in United States foreign policy; and arms control.
Includes bibliographical references.
ne 17/05/2018
Loan
Keywords: Policy sciences; United States